Identification of Riparian Plants Potential for Remediation and Water Quality Monitoring in The Downstream of Brantas River, East Java - Irawanto, Rony; Afifudin, Alfin Fatwa M (SCISCITATIO, 2024)
Indonesia is home to an extraordinarily diverse range of plant and animal species, particularly in vital wetland, riparian, and aquatic areas crucial for watershed ecosystems. For example, the Brantas River system, located in East Java, plays a pivotal role in sustaining regional biodiversity. However, the river system is currently under threat from degradation and escalating river pollution. This underscores the pressing need to document and inventory its plant diversity. This study specifically focuses on the downstream area of the Brantas River, aiming to identify riparian seed-plants and assess their potential in remediating pollutants. Additionally, the research evaluates water quality in the downstream region. Conducted from November 2020 to February 2021 using an observational method with a descriptive explorative approach, the studyidentified 14 seed-bearing plant species in the downstream area. Although certain water quality parameters met established standards, elevated levels of heavy metals such as lead, copper, and chromium exceeded permissible limits. Notably, 12 out of the 14 identified plant species demonstrated the ability to absorb heavy metals from the environment.